Literatura polska w słowackich przekładach po 2007 roku - Buczek, Marta (Przekłady Literatur Słowiańskich, 2014)
Polish Literature in Slovak translations after 2007 Marta Buczek — the author of the article Polish Literature in Slovak translations after 2007 describes in detail the Polish literature which was translated in Slovakia in the years 2007—2013. In her article she also deals with contemporary Slovak publishers market which publishes translations of Polish literature, Slovak publishers and Slovak translators. She analyzes translation literature with view of its entry into a new literary context. Key words: Polish literature in Slovak translation, Polish literature in Slovakia, Slovak translators of Polish literature, Slovak publishers of Polish literature, literary translation.